Dental Caries Experience in 6-13 Years Old School Children of Dharan Sub-Metropolitan City, Nepal: A Cross-Sectional Study - Bastola, Bhawana Sigdel; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha; Baral, Dharanidhar (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Introduction: Dental caries though preventable oral health problem is affecting school children worldwide and around 50% of Nepalese children are suffering from it. Baseline data with good understanding of dental caries and associated risk factors are necessary to form preventive strategies for setting and achieving oral health goals. Objective: This study was conducted to determine dental caries experience and associated risk factors among school-going children of 6-13 years old in Dharan sub-metropolitan city, Nepal. Methods: A cross-sectional study was conducted from 5th Jan 2018 to 4th Jan 2019 among 680 school children selected by multistage cluster sampling method. Pretested, standardized, closed-ended questionnaire answered by the parents was used to gather information regarding the associated risk factors. Dental caries experience was obtained from deft/DMFT (WHO modification 1997). Comparison of categorical data was done using Chi-square test. Multivariable binary logistic regressions were used for the statistical analysis. Results: The overall caries prevalence was 61.6%, in primary dentition it was 48.25% and in permanent dentition it was 34.4%. Dental caries experience was with mean deft 4.67 (±2.7) in primary dentition and mean DMFT 1.72 (±1.05).in permanent dentition. Multivariate analysis showed significant association between dental caries experience and grade three and grade four school children had experienced greater caries (p<0.05, OR =2.7). Dental caries was associated with eating sweets at night (p<0.001, OR=2.5) and snacking in-between meals (p<0.001, OR=2.5). Conclusions: Dental caries among school-children in Dharan showed a significant burden especially within the primary dentition. It was significantly associated with factors like feeding habits -eating sweets in a day, eating sweets at night and snaking in between meals